Heterometallic Inorganic-Organic Frameworks of Sodium-Bismuth Benzenedicarboxylates - Thirumurugan, A; Tan, J; Cheetham, A (2010)
Four three-dimensional (3D) inorganic-organic heterometallic Na-Bi benzenedicarboxylate (BDC) frameworks, [NaBi(1,4-BDC)2(DMF) 2], 1, [NaBi(1,4-BDC)2(DMF)(H2O)](DMF), 2, [NaBi(1,3-BDC)2(DMF)], 3, and [NaBi(1,3-BDC)2(EtOH)], 4, have been synthesized under solvothermal conditions and their structures were determined by single crystal X-ray diffraction. Compounds 1 and 2 have very similar channel structures in which infinite Na'O'Bi chains of one-dimensional inorganic connectivity are linked by the 1,4-BDC anions into 3D structures (I1O2). Compound 2 was obtained from 1 when it was exposed to moisture; it becomes amorphous when the solvent is removed from the channels on heating, but the activated phase has a reasonably high surface area of 71 m2/g from nitrogen porosimetry measurements. Compounds 3 and 4 are isostructural except for the solvents; they contain Na'O'Bi layers that are linked into 3D structures (I2O1) by 1,3-BDC anions. They are robust owing to their two-dimensional inorganic connectivity and retain their framework structures even after the removal of the solvent molecules from the channels. However, the surface area of an activated sample of 3 is only 8 m2/g due to the narrow apertures into the cavities. Tb3+- and Eu3+-doped 2 and 3 emit characteristic ligand-sensitized green and red luminescence, respectively. © 2009 American Chemical Society.